2004
DOI: 10.1515/cclm.2004.147
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress: potential of distinct peroxide determination systems

Abstract: When reactive oxygen species attack biological structures, peroxides, which are short-lived oxidative intermediates, are generated. We evaluated the potential of two different, commercially available peroxide activity assays (Pox-Act and d-ROMS) to see whether the results were associated with the clinical condition of subjects who were participating in a routine health care program. Furthermore, we determined the total antioxidant status (TAS) and the titer of autoantibodies against oxidized low-density lipopr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Moreover, it is not affected by the significant changes of serum antioxidants and mainly those of uric acid concentration during dialysis, as applies to other TAC oxidative markers such as TAC and FRAP [5,22] . On the other hand, in a previous study the sensitivity of d-ROMs has been found lower in comparison with that of Pox-Act assay, which evaluates the concentration of total peroxides via a peroxidase reaction [23] . However, the diverse clinical profile of patients participating in the above study and the lack of evidence about a direct correlation of Pox-Act with other markers of oxidative stress, made the selection of d-ROMs preferable for our report, without excluding a prospective complementary use of the former test.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, it is not affected by the significant changes of serum antioxidants and mainly those of uric acid concentration during dialysis, as applies to other TAC oxidative markers such as TAC and FRAP [5,22] . On the other hand, in a previous study the sensitivity of d-ROMs has been found lower in comparison with that of Pox-Act assay, which evaluates the concentration of total peroxides via a peroxidase reaction [23] . However, the diverse clinical profile of patients participating in the above study and the lack of evidence about a direct correlation of Pox-Act with other markers of oxidative stress, made the selection of d-ROMs preferable for our report, without excluding a prospective complementary use of the former test.…”
Section: Discussionmentioning
confidence: 70%
“…This possibility seems credible because an almost identical pattern of progression of levels of sICAM-1 and total peroxides (r = 0.92) has been observed in our patients indicating a strong link between the two parameters. The determination of serum peroxides might therefore be simple and useful method for the estimation of the persistence of systemic oxidative stress during convalescence following severe acute disorders in cardiovascular systems, as also suggested by Lindschinger et al (2004).…”
Section: Discussionmentioning
confidence: 92%
“…The test system was based on a peroxide/peroxidase reaction using 3,5,3´,5´-tetramethylbenzidine (TMB) as substrate. Reference values were reported to be less than 200 µM (Lindschinger et al 2004). Peroxide levels were evaluated as arbitrary units with a CV of 3.73% (intra-assay variance) and 5.51% (inter-assay variance), and expressed as percentage of baseline.…”
Section: Serum Total Peroxidesmentioning
confidence: 99%